2011
DOI: 10.4254/wjh.v3.i7.198
|View full text |Cite
|
Sign up to set email alerts
|

An extended treatment protocol with pegylated interferon and ribavirin for hepatitis C recurrence after liver transplantation

Abstract: Recurrent HCV after LT can be safely treated with extended virological response-guided therpy using PEG/RBV, but requires close monitoring for treatment-related adverse effects, particularly cytopenias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In their study, 15% of patients necessitated RBV dose reductions compared with approximately 40% of patients (range of between 24% and 92%) when PIFN/RBV was administered concurrently in studies evaluating similar patient populations post transplant. 24 , 25 , 26 , 27 , 28 Their study also demonstrated that RBV priming results in improved SVR rates compared with results of published trials performed using standard combination therapy −46% vs. 29% respectively. 23 , 26 While our study was discontinued prior to collection of SVR data, mean log 10 reductions from baseline in HCV RNA were significantly greater in the pre-dosing vs. the standard dosing arm at Day 1 [−0.34 ± 0.46 vs. 0.09 ± 0.32 ( P ≤ 0.003)].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In their study, 15% of patients necessitated RBV dose reductions compared with approximately 40% of patients (range of between 24% and 92%) when PIFN/RBV was administered concurrently in studies evaluating similar patient populations post transplant. 24 , 25 , 26 , 27 , 28 Their study also demonstrated that RBV priming results in improved SVR rates compared with results of published trials performed using standard combination therapy −46% vs. 29% respectively. 23 , 26 While our study was discontinued prior to collection of SVR data, mean log 10 reductions from baseline in HCV RNA were significantly greater in the pre-dosing vs. the standard dosing arm at Day 1 [−0.34 ± 0.46 vs. 0.09 ± 0.32 ( P ≤ 0.003)].…”
Section: Discussionmentioning
confidence: 74%
“…They demonstrated that RBV priming both enhanced efficacy and improved adherence, and proposed that by administering medications in this sequential manner, patients have time to adjust to the side effects of each medication. In their study, 15% of patients necessitated RBV dose reductions compared with approximately 40% of patients (range of between 24% and 92%) when PIFN/RBV was administered concurrently in studies evaluating similar patient populations post transplant . Their study also demonstrated that RBV priming results in improved SVR rates compared with results of published trials performed using standard combination therapy −46% vs. 29% respectively .…”
Section: Discussionmentioning
confidence: 87%